2020
DOI: 10.3390/rs12244133
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Prediction of Typhoon-Induced Rainfall over China Using Historical Rainfall, Tracks, and Intensity of Typhoon in the Western North Pacific

Abstract: Typhoons or mature tropical cyclones (TCs) can affect inland areas of up to hundreds of kilometers with heavy rains and strong winds, along with landslides causing numerous casualties and property damage due to concentrated precipitation over short time periods. To reduce these damages, it is necessary to accurately predict the rainfall induced by TCs in the western North Pacific Region. However, despite dramatic advances in observation and numerical modeling, the accuracy of prediction of typhoon-induced rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 32 publications
2
28
1
Order By: Relevance
“…Similarly, to forecast typhoon rainfall, some studies applied this distance as input for statistical models (Kim et al., 2020; Lonfat et al., 2007; Tuleya et al., 2007). Moreover, several studies have defined typhoon rainfall events that occurred within a 500 km radius from the typhoon center to show the contribution of typhoon rainfall to total rainfall (F. J. Chen & Fu, 2015; Dare et al., 2012; Hernández Ayala & Matyas, 2018; Jiang & Zipser, 2010; Larson et al., 2005; Lau et al., 2008; Lavender & Abbs, 2013; Lee et al., 2010; Nogueira & Keim, 2011; Prat & Nelson, 2013a, 2013b; Schreck et al., 2011; Uddin et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, to forecast typhoon rainfall, some studies applied this distance as input for statistical models (Kim et al., 2020; Lonfat et al., 2007; Tuleya et al., 2007). Moreover, several studies have defined typhoon rainfall events that occurred within a 500 km radius from the typhoon center to show the contribution of typhoon rainfall to total rainfall (F. J. Chen & Fu, 2015; Dare et al., 2012; Hernández Ayala & Matyas, 2018; Jiang & Zipser, 2010; Larson et al., 2005; Lau et al., 2008; Lavender & Abbs, 2013; Lee et al., 2010; Nogueira & Keim, 2011; Prat & Nelson, 2013a, 2013b; Schreck et al., 2011; Uddin et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, to forecast typhoon rainfall, some studies applied this distance as input for statistical models (Kim et al, 2020;Lonfat et al, 2007;Tuleya et al, 2007). Moreover, several studies have defined typhoon rainfall events that occurred within a 500 km radius from the typhoon center to show the contribution of typhoon rainfall to total rainfall (F. J.…”
Section: Select Data Within a 500 Km Radius From The Typhoon Centermentioning
confidence: 99%
“…There are mainly two reasons for the best performance of the current study. First, the input variable-typhoon rainfall within a 500 km radius-helps this study to yield more accurate forecasts than existing models, as earlier studies (e.g., Kim et al, 2020;Lonfat et al, 2007;Tuleya et al, 2007) confirmed the advantage of this input in their statistical models. Second, the parameterization technique (grid-search cross-validation) helps this study to find the best parameters for SVM, RF, AdaBoost, CNN, and LSTM models, as in previous studies (e.g., Noori et al, 2011;Wu et al, 2008Wu et al, , 2019Yu et al, 2006) reported in their flood and streamflow forecasting models that this method was simple, robust, and time-saving.…”
Section: Comparison Between the Existing Models And The Proposed Modelmentioning
confidence: 71%
“…The reason to use a 500 km radius from the typhoon center as input is that the range of the typhoon's primary wind circulation region (80-400 km radius) and the curved typhoon cloud shield (550-600 km radius) is consistent with a 500 km radius from the typhoon center (Englehart & Douglas, 2001). The importance of using typhoon rainfall within this distance as input to forecast typhoon rainfall was confirmed by statistical models (Kim et al, 2020;Lonfat et al, 2007;Tuleya et al, 2007). Moreover, previous studies related to the contribution of typhoon rainfall to total rainfall also recognized typhoon rainfall events that occurred within a 500 km radius from the typhoon center (F. J.…”
mentioning
confidence: 92%
“…This problem can be largely attributed to the lack of sufficient high-performance computing resources (Bachmann & Torn, 2021;Judt, 2018;Selz, 2019) and the limited ability to parameterize sophisticated TC rainfall physical processes in NWP models; significant progress in both cannot be achieved in a short period. Therefore, some scientists have aimed to fill in this gap by exploring TC rainfall forecasts with statistic-or analog-based techniques (Bagtasa, 2021;Li et al, 2015;Kim et al, 2019Kim et al, , 2020Ren et al, 2018;Wei, 2012aWei, , 2012bZhong et al, 2009).…”
mentioning
confidence: 99%